A method for rearing Fuller’s rose weevil, Naupactus cervinus (Coleoptera: Curculionidae) on an artificial diet - Clare, Graeme; Husheer, Sean (New Zealand Plant Protection, 2026)
Fuller’s rose weevil, Naupactus cervinus (Boheman) (Coleoptera, Curculionidae) adults are only available in the field for a short period of time each year. As field-collected insects are not of a known standardised quality or age, they are not suitable for experimental work. Our goal was to develop a laboratory rearing technique to enable access to all life stages of this insect year-round. This paper reports on life-cycle data for two generations of Naupactus cervinus reared on an artificial diet. Key life cycle parameters were determined, and a laboratory colony was successfully established. The life cycle parameters at 20°C and an 18-h photoperiod were as follows: the egg development period was approximately 30 days, the neonate-to-adult period was about 21 weeks, and the average generation time (egg to egg) was approximately 27 weeks. The diet and rearing technique enabled the year-round, laboratory rearing of standardised adult insects of known quality and age, with larvae fed artificial diet and adults fed mature citrus leaves for two successive generations.